Bridging Therapies With Injectable Immunomodulatory Drugs in the Management of Multiple Sclerosis: A Delphi Survey of an Italian Expert Panel of Neurologists - Marfia, Girolama Alessandra; Centonze, Diego; Salvetti, Marco; Ferraro, Elisabetta; Panetta, Valentina; Gasperini, Claudio; Mirabella, Massimiliano; Conte, Antonella (Frontiers in Neurology, 2022)
Background In multiple sclerosis (MS), bridging therapies are usually administered when switching from one therapy to another. Such treatments generally consist of injectable immunomodulatory drugs (interferon or glatiramer acetate), whose efficacy, safety, and tolerability data are consolidated for use even in fragile patients. We performed a nationwide survey to gather expert opinions regarding the most appropriate use of bridging therapies in MS. Methods An independent steering committee of Italian neurologists with expertise in MS treatment identified critical issues in the use of bridging therapies and formulated a questionnaire. This questionnaire was used to conduct a Delphi web survey, involving a panel of Italian neurologists with experience in MS treatment. Their anonymous opinions were collected in three sequential rounds. Consensus was defined as an interquartile range (IQR) ≤2. Results Responses were obtained from 38 experts (100%) in all three rounds. Injectable immunomodulatory drugs were considered first-line therapy in patients with mild-to-moderate disease activity and in women planning to become pregnant. In addition, the experts were confident about prescribing these drugs in patients at risk of cancer recurrence, while the panel agreed to discontinue any treatments in patients with uncontrolled cardiovascular or metabolic disorders. Moreover, bridging therapy with injectable immunomodulatory drugs was considered appropriate in order to protect the patient from disease reactivation when a prolonged washout was needed and also while waiting for the completion of the immunization schedule. Conclusion The results of this nationwide survey confirm that, among Italian neurologists, there was wide agreement on the use of bridging therapies with injectable immunomodulatory drugs in several conditions in order to minimize the risk of disease reactivation when a prolonged washout was required or when the immunization schedule still needed to be completed in patients planning to become pregnant and in patients at risk of cancer recurrence.